2021
DOI: 10.1021/acs.nanolett.0c04596
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Folding Growth of Graphene on h-BN

Abstract: Graphene has been the subject of much research, with structural engineering frequently used to harness its various properties. In particular, the concepts of graphene origami and kirigami have inspired the design of quasi-three-dimensional graphene structures, which possess intriguing mechanical, electronic, and optical properties. However, accurate controlling the folding process remains a big challenge. Here, we report the discovery of spontaneous folding growth of graphene on the h-BN substrate via adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…[100] In 2021, Fan et al reported the spontaneous folding growth of graphene on the h-BN substrate at a growth temperature up to 1300 °C using CVD method. [101] Comparison of different preparation methods for tBLG is provided with respect to its costs, uniformity, variability, cleanness, and productivity, as shown in Figure 12. With relative orientation and interlayer coupling, tBLG can be obtained by i) CVD growth on metal substrates (Figure 12a), ii) man made stacking graphene layer on each other (Figure 12b), or iii) artificial folding (Figure 12c).…”
Section: Other Preparation Methods Of Tblgmentioning
confidence: 99%
“…[100] In 2021, Fan et al reported the spontaneous folding growth of graphene on the h-BN substrate at a growth temperature up to 1300 °C using CVD method. [101] Comparison of different preparation methods for tBLG is provided with respect to its costs, uniformity, variability, cleanness, and productivity, as shown in Figure 12. With relative orientation and interlayer coupling, tBLG can be obtained by i) CVD growth on metal substrates (Figure 12a), ii) man made stacking graphene layer on each other (Figure 12b), or iii) artificial folding (Figure 12c).…”
Section: Other Preparation Methods Of Tblgmentioning
confidence: 99%
“…Reproduced with permission. [ 60 ] Copyright 2021, American Chemical Society. h,i) Schematic illustrations of the electron transfer mechanisms in h) WS 2 /MoS 2 and i) MoS 2 /WS 2 vertical vdWHs under irradiation, respectively.…”
Section: Controllable Synthesis Of 2d Vdwhs and Vdwslsmentioning
confidence: 99%
“…[ 59 ] In particular, the CVD process provides a controllable way to construct graphene origami and kirigami, which are quasi‐3D graphene structures with intriguing mechanical and electronic properties. Fan et al [ 60 ] found that the noncatalytic bulk h‐BN substrate played a significant role in the spontaneous folding of graphene by facilitating the appearance of the second layer on the existing ML graphene surface (Figure 3g). The faster growth rate for the second graphene layer compared to the first layer resulted in overtaking growth to form folded edges at a growth temperature of up to 1300 °C.…”
Section: Controllable Synthesis Of 2d Vdwhs and Vdwslsmentioning
confidence: 99%
“…To prepare a highly efficient cooling coating, evenly distributed and controllable coordinated Gr/ h -BN filler was considered prominently. Graphene and h -BN filler can be prepared by several methods, including the mixing of Gr and h -BN by mechanical dispersion or sonification, chemical vapor deposition (CVD) by metal catalyst, and graphene fabricated on h -BN in CH 4 /H 2 or CO 2 atmosphere. Combustion synthesis of graphene was reported as being accessible and energy-saving, and the graphene synthesized by this method is of high quality with fewer layers . As we know, in situ growth of graphene on an h -BN surface is promising to form ideal coordinates by van der Waals interactions through the vertical orientation, which shows improved thermal conductivity compared with conventional graphene for heat dissipation.…”
Section: Introductionmentioning
confidence: 99%